Model Pendidikan Berwawasan Kebangsaan bagi Anak Usia Dini sebagai Sarana Integrasi Bangsa - Ubaidillah (Atthiflah: Journal of Early Childhood Islamic Education, 2019)
Paud is one of the most important things in building one's future, because success in Paud will have an impact on the progress of a nation. At this age the structure and function of the brain is developing and its influence is sedentary to the further development of children's behavior and personality. So they are very appropriate if used as an initial community formation of national character. Nationality-oriented education in Early Childhood (AUD) is expected to prepare them to become someone who has an identity both in local and global communities, and has a vision to build a world together in a global culture. One way for children to receive subject matter (for kindergarten subject matter using themes), is through games. These games include traditional games. In traditional games, we can develop a sense of togetherness, mutual cooperation, reducing selfishness, etc. Playing on children has a very important meaning because through playing children experience development in all aspects of their lives, however, the challenge now is the game tools and hero figures from other countries that affect children a lot, addressing this need for change by instilling insight nationality in play activities and educational game tools used by early childhood, and try to connect the forms of games or activities with aspects that are developed. nationalism-oriented education model in early childhood education uses a thematic approach, so through this theme various kinds of children's potential can be developed, national values ??that want to be socialized and transformed in learning activities in an integrated manner developing abilities, physical motoric, skills, cognitive, science, art, language and habituation, using learning activities that are designed with the concept of learning while playing.